Analysis of Energy Intensity Decomposition in the Textile Industrial Sub Sector of Indonesia - Salamah, Sally; Zakaria, Wan Abbas; Gunarto, Toto; Hamzah, Lies Maria; Said, Muhammad (International Journal of Energy Economics and Policy, 2019)
The purpose of this study was to analyze the energy intensity decomposition in the textile industry subsector of Indonesia at level 2 and 3 KBLI. This is because of its usefulness in measuring energy efficiency. However, energy decomposition has not been able to accurately reflect the efficiency that occurs in the industrial sector. Since the results gotten from the calculation of energy intensity contains components of structural factors, there is need for the analysis of the changes in the composition of output caused by activities or a combination of output and energy intensity components. Energy intensity approach and the Time Series technique through the use of log mean divisia index I method was used in this study to determine the effect of structural and intensity factors on changes in aggregate energy intensity in the textile industry sector in Indonesia. The results showed that the energy intensity of the textile industry between 2006 and 2014 experienced a downward trend, but the structural factors were more dominant than the intensity factor. Therefore, there is need for structural factors in energy intensity decomposition of the textile industry sector so as to be able to save energy. Keywords: Energy Intensity, Structural Effect, Intensity Effect; Decomposition, Textile Industry, Indonesia JEL Classifications: L67, Q4 DOI: https://doi.org/10.32479/ijeep.7457